Surrogate mothers: forensic medicine reflections about the defence of the embryo, the unborn child, the "two mothers", and the dignity of the human person - Albertazzi, Gianluca; Vetrugno, Giuseppe; Sacchini, Dario (Medicina e Morale, 2000)
In the last few years, the new reproductive technologies - particularly the so-called "surrogate motherhood" technology - determined a series of moral, social, and juridical implications, which have been involving not only the problem of the child born through non natural means, but also the problem of motherhood. On the 14th of February 2000, a judge of the Tribunal of Rome (XI Civil Section) promulgated a decree authorizing a gynecologist to transfer cryopreserved embryos, obtained by the fusion of the gametes of two spouses' gametes, into another woman's uterus, who volunteered to carry out pregnancy for free, despite the prohibition of the Italian Code of Medical Ethics. The Republic Attorney's Office of the Tribunal of Rome and the National Federation of Medical Surgeons and Odontologists Council appealed against the decree, but the Tribunal of Rome (XI Civil Section) judged the appeal inadmissible on the 30th of March, confirming in fact the effect of the decree. Finally, on the 10th of May, the couple decided to undergo the surrogate motherhood in countries where this practice is permitted. The Authors go over this judiciary event in order to discuss the delicate issue of surrogate motherhood practice, by examining the content of the decree and dealing with the forensic medicine aspects, in the light of both Italian and international doctrine, law, and bioethics on this issue.